The Role of Early Childhood Education Teachers in Preparing Early Childhood Learning Readiness in the Transition Period - Hanifah, Siti; Euis Kurniati; Rudiyanto (Universitas Pendidikan Ganesha, 2024)
The transition from Early Childhood Education (ECE) to primary school is a critical stage in the development of young children. The role of ECE teachers in preparing children's readiness for learning during this transition period is key to ensuring a successful adaptation to a new environment and more complex academic demands. This study aims to thoroughly evaluate the role of ECE teachers in supporting school readiness among young children during the transition from ECE to primary school. This research employs a descriptive qualitative method, using interviews as the primary data collection technique. The study involved three ECE teachers as participants. Data were analyzed using thematic analysis. The findings indicate that ECE teachers play a vital role in developing children's social, emotional, academic, and self-reliance skills during the transition period. They create supportive learning environments, introduce basic concepts, foster independence, and provide emotional support to the children. ECE teachers contribute to building a strong foundation for children's academic success in primary school. The implications of this study highlight the importance of emphasizing the role of ECE teachers in preparing children for the changes they face when entering a new phase in their education. A deeper understanding of the role of ECE teachers can help enhance early childhood education, ensuring a more meaningful and supportive learning experience for children during the transition to primary school.